Can Intra-Regional Trade Act as a Global Shock Absorber in Africa? - Zuzana Brixiova; Qingwei Meng; Mthuli Ncube (Institute for the Study of Labor (IZA), 2015)
The global financial crisis and the subsequent uneven recovery have underscored the need for Africa's resilience to output and other shocks originated in the rest of the world. A comparison of two regional economic communities the East African Community (EAC) and the Southern Africa Customs Union (SACU) suggests that deeper intra-regional, and in particular intra-industry, trade ties have contributed to the EAC's resilience to external output shocks. More broadly, intra-regional and intra-African trade with fast-growing economies, together with geographically diversified trade links, can strengthen the capacity of African countries to absorb global output shocks. Besides helping shield countries from external shocks, intra-regional trade also supports economic diversification and participation in regional value chains.
Keywords: E32; F4; F15; 330; regional economic communities; output co-movement; intra-regional trade; Africa